STRETCHING THE INFLUENCE OF PERFORMANCE ATHLETES OF FOOTBALL (Fiep Bulletin - online, 2013)
The search for extracting the maximum capacity of the athlete has piqued the interest of various professionals, including the physiotherapist. Among the resources used to strengthen the muscular action, warming has already proven. Stretching, however, has generated discussion about its role in athletic performance. The present study aims to relate static stretching and athletic performance in sports. For this, we selected soccer players who work in under-18 category, ages 15 and 18. The study participants underwent tests of agility, strength and speed in two days, and only on the first and second heating with heating associated with stretching. The results obtained in the tests showed that the active static stretching has little or no influence on the performance of the athlete. Specific studies are needed to determine the type of elongation best fits the activity of which is required to improve performance
Keywords: Stretching; performance; strength; agility; speed